Pendampingan Pembuatan Nomor Induk Berusaha bagi Pelaku Usaha Mikro, Kecil dan Menengah - Kurnia Harlina Dewi; Rahayu, Lisa (Insan Kreasi Media, 2024)
Nagari Kinari is a village located in Bukit Sundi District, Solok Regency which was developed into a natural tourist destination, one of which is the tourist attraction “Batu Barajuik”. This condition is a good opportunity for the community to improve the economy through local-based Micro, Small and Medium Enterprises (MSMEs). MSMEs in Nagari Kinari in selling their products require business legality or Business Identification Number (NIB), Home Industry Food Production Certificate (SPP-PIRT) and Halal certificate. So that the product produced can be marketed widely and provide a guarantee of safety for consumers. Business Identification Number (NIB) is the identity of the business license issued by the OSS (Online Single Submission). The Department of Agricultural Industrial Technology conducts a community service program to provide wider knowledge to the community and assist in making NIB which is then carried out by handing over NIB documents to the community of MSME. The method implemented is training in making NIB based on OSS, discussion, and submission of NIB. The result of these activities is the issuance of NIB documents, which are then delivered by the Head of the Department of Agricultural Industrial Technology to business actors.